Pengaruh Permainan Memancing Terhadap Kemampuan Mengenal Lambang Bilangan Anak Usia 5-6 Tahun Di Tk Permata Hati Hutagalung (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The aim of this research is to determine the Influence of Fishing Game on the Ability to Recognize Number Symbols in 5-6-Year-Old Children at Permata Hati Hutagalung Kindergarten. The research method used is a quantitative descriptive and inferential method. The population consists of 30 children aged 5-6 years at Permata Hati Hutagalung Kindergarten, and the entire population is used as respondents in the study. Data was collected using a closed positive questionnaire with 30 items, 15 for variable X and 15 for variable Y. The data analysis results indicate that there is an Influence of the Fishing Game on the Ability to Recognize Number Symbols in 5-6-Year-Old Children at Permata Hati Hutagalung Kindergarten: 1) Analysis of requirements: a) The test for a positive relationship obtained a value of rxy = 0.473, which is greater than the table value (α=0.05, n=30) = 0.361. b) The test for a significant relationship obtained a calculated t-value of 2.042, which is greater than the table value (α=0.05, df=n-2=28) = 2.048. 2) Influence test: a) Regression equation test resulted in the regression equation Y ̂="2" 0",22"+0,61X. b) The coefficient of determination (r^2) for the regression is 22.4%. 3) Hypothesis test using an F-test resulted in Fcalculation > Ftable (α=0.05, numerator df k=11, denominator df=n-2=30-2=28), which is 8.05 > 2.09. Therefore, Ha is accepted, and H0 is rejected.